Pengaruh Kemampuan Pemahaman Konsep Matematis dan Kecemasan Matematika Terhadap Kemampuan Koneksi Matematis Siswa - Rahmawati, Dea; Mardhiyana, Dewi (Imajiner: Jurnal Matematika dan Pendidikan Matematika, 2025)
This study aims to determine three things, namely (1) the effect of mathematical concept understanding ability on students' mathematical connection ability, (2) the effect of math anxiety on students' mathematical connection ability, and (3) the effect of mathematical concept understanding ability and math anxiety on students' mathematical connection ability. This research used quantitative research method with ex post facto research type. The research population included all 11th grade students of SMA Negeri 1 Petarukan. The sample selection was conducted using cluster random sampling technique. The selected sample was class XI IKM 11 with 35 students. Data collection techniques were carried out using test instruments and questionnaire instruments. The data analysis technique was carried out through two stages, namely simple linear regression test and multiple linear regression test. The conclusion of this study, namely (1) the ability to understand mathematical concepts has a positive and significant effect on students' mathematical connection skills by 76.49%, (2) math anxiety has a negative and significant effect on students' mathematical connection skills by 75.80%, and (3) the ability to understand mathematical concepts and math anxiety has a positive and significant effect on students' mathematical connection skills by 81.60%.